2021
DOI: 10.3397/in-2021-1435
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on acoustics and efficiency of rotor configurations for electric aerial vehicles

Abstract: Aerial vehicles based on distributed electric propulsion systems have gained great interest. Their rotors however create loud and annoying sound, what obstructs market success. Variations in rotor configuration can be observed on emerging concepts, whereby the main varied parameters are blade radius, number of blades and blade distribution. The focus of this paper is to identify how these parameters can be chosen to optimize efficiency and acoustics, including psychoacoustic metrics and sound quality of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is important to take care not only of the outdoors environmental drone noise distribution near the flight path but the noise levels on the façade and the noise levels transmitted inside the buildings [ 4 ]. The literature on drone noise emission has reported that drone noise signature is highly influenced by the type of drone configuration, e.g., number of rotors in multi-copters, size and weight, flight manoeuvres [ 5 , 6 , 7 , 8 ], and also significantly influenced by the ambient weather conditions, most notably the wind [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to take care not only of the outdoors environmental drone noise distribution near the flight path but the noise levels on the façade and the noise levels transmitted inside the buildings [ 4 ]. The literature on drone noise emission has reported that drone noise signature is highly influenced by the type of drone configuration, e.g., number of rotors in multi-copters, size and weight, flight manoeuvres [ 5 , 6 , 7 , 8 ], and also significantly influenced by the ambient weather conditions, most notably the wind [ 9 ].…”
Section: Introductionmentioning
confidence: 99%